Effects of Salt Reduction and the Inclusion of Seaweed (Kappaphycus alvarezii) on the Physicochemical Properties of Chicken Patties - Wolyna Pindi; Lim Wei Qin; Nurul Shaeera Sulaiman; Hana Mohd Zaini; Elisha Munsu; Noorakmar Ab Wahab; Nor Qhairul Izreen Mohd Noor (Molecular Diversity Preservation International (MDPI), 2023)
This study investigates the effect of salt reduction through the inclusion of seaweed (Kappaphycus alvarezii) on the physicochemical and sensory qualities of chicken patties. A control sample (1.5% salt and without seaweed) and four chicken patty formulations were used with two levels of salt (1% and 1.5%) and two levels of seaweed (2% and 4%). Adding seaweed improves water holding capacity and minimized cooking loss in reduced-salt patties. In addition, adding seaweed decreases the shrinkage of the diameter and thickness of chicken patties (p > 0.05). However, adding seaweed made the patties darker, as shown by lower L* values (p > 0.05). Additionally, the incorporation of seaweed significantly increased (p < 0.05) the hardness, chewiness, cohesiveness, and elasticity of patties. Reduced-salt chicken patties with the addition of 2–4% of seaweed showed lower extracted water than 1.5% salt chicken patties with seaweed (p < 0.05), indicating a higher water holding capacity. The sensory evaluation showed that the chicken patty with 1.5% salt and 4% seaweed had the highest overall acceptability. However, the overall acceptability of the chicken patties with 1% salt and 4% seaweed was significantly higher (p < 0.05) than the control. In conclusion, the addition of Kappaphycus alvarezii to reduced salt patties improved textural properties with acceptable taste profiles.